Machine Learning Identifies Metabolic Signatures that Predict the Risk of Recurrent Angina in Remitted Patients after Percutaneous Coronary Intervention: A Multicenter Prospective Cohort Study. Issue 10 (8th March 2021) - Cui, Song; Li, Li; Zhang, Yongjiang; Lu, Jianwei; Wang, Xiuzhen; Song, Xiantao; Liu, Jinghua; Li, Kefeng
Abstract: Recurrent angina (RA) after percutaneous coronary intervention (PCI) has few known risk factors, hampering the identification of high‐risk populations. In this multicenter study, plasma samples are collected from patients with stable angina after PCI, and these patients are followed‐up for 9 months for angina recurrence. Broad‐spectrum metabolomic profiling with LC‐MS/MS followed by multiple machine learning algorithms is conducted to identify the metabolic signatures associated with future risk of angina recurrence in two large cohorts ( n = 750 for discovery set, and n = 775 for additional independent discovery cohort). The metabolic predictors are further validated in a third cohort from another center ( n = 130) using a clinically‐sound quantitative approach. Compared to angina‐free patients, the remitted patients with future RA demonstrates a unique chemical endophenotype dominated by abnormalities in chemical communication across lipid membranes and mitochondrial function. A novel multi‐metabolite predictive model constructed from these latent signatures can stratify remitted patients at high‐risk for angina recurrence with over 89% accuracy, sensitivity, and specificity across three independent cohorts. Our findings revealed reproducible plasma metabolic signatures to predict patients with a latent future risk of RA during post‐PCI remission, allowing them to be treated in advance before an event. Abstract : Plasma metabolomics followed by multiple machine learning algorithms and quantitative analysis is conducted to identify recurrent angina‐related alternations that reflect only a small subset of the plasma metabolome from cohort‐specific effects. This approach allows to develop and validate a robust and reproducible metabolic predictive model that can prospectively identify the future risk of angina recurrence across three independent cohorts.